Social Entrepreneur’s Psychological Capital, Political Skills, Social Networks and New Venture Performance - Guo, Li Xin; Liu, Chi-Fang; Yain, Yu-Sheng (Frontiers in Psychology, 2020)
Scholars have begun to realize the importance of entrepreneurial political skills to new ventures. Namely, social entrepreneurship is a context, in which entrepreneurs expend great efforts in networking politically to integrate diverse resources and share interests (e.g., ecology wellness) for sustainability. In this paper, we integrate the social exchange theory and the resource-based view to discuss how social entrepreneurs’ political skills enhance new ventures’ performance through their social network (size/diversity and structural holes), and discuss how psychological capital in entrepreneurial contexts can influence new venture performance by political skills’ functionality. By connecting significant entrepreneurship research constructs at different levels, this article not only enriches our knowledge about the ways in which social entrepreneurs’ political skills and psychological capital affect the performance of ventures, but also offers new ventures some guidance on how to use political skill to improve their social networking and performance. Implications for social entrepreneurial sustainability are discussed.